دراسة تغيرات محتوى ومستوى الماء الأرضي وخصائص التربة الفيزيائية والهيدروديناميكية في تربة مزرعة بوقا - إبراهيم, جهاد; اسكيف, جينا (Latakia University Journal -Biological Sciences Series, 2018)
The study of ground water in the heavy clay soil which is scattered in the Syrian coast showed that the ground water level depth ranged from 88-144 cm during the year 2015-2016. It also showed that the ground water content of calcium, sodium and Magnesium was good and the SAR, R.S.P values ​​were within the normal limits for the water to irrigate the plants. As the unsaturated hydraulic conductivity of the infrastructure soil layers is ranged between 0.11-.00052 m \ Day at the moistness values pF were between 1.3 - 3.51, and the largest air porosity was from 10 microns outside the harmful border for the growth of the plants to a depth of 60 cm and the pores that contain available water decrease with the increasing of depth from 13.52 to 10. 27, as the values ​​of the hydraulic constants of the soil were ( d= 1.0153, c= 464.3 , b= 10.142 a= 0.0083) and they are the constants which give good indications of the possibilities to use the ground water. أظهرت الدراسة التي أجريت على تغيرات محتوى ومستوى الماء الأرضي في تربة طينية منتشرة في الساحل السوري أن عمق مستوى الماء الأرضي تراوح بين 144-88سم خلال العام 2016-2015.كما تبين أن محتوى الماء الأرضي من الكالسيوم والمغنيزيوم كان جيداً وأن قيم SAR وR.S.P كانت ضمن الحدود الطبيعية لصلاحية المياه لري النباتات. كما تراوح معامل التوصيل الهيدروليكي غير المشبع لطبقات التربة التحتية الناقلة بين 0.00052-0.11 م/يوم عند قيم شد رطوبيpF بين 3.51-1.3، وكانت المسامية الهوائية الأكبر من 10ميكرون خارج الحدود الضارة لنمو النبات حتى العمق 60سم والمسامات التي تحوي ماء متاح تقل مع زيادة العمق من 10.27إلى13.52 كما بلغت قيم الثوابت الهيدروديناميكية للتربة(a=0.0083 , b=-10.142 , c=464.3 , d=-1.0153 ) وهي ثوابت تعطي مؤشرات جيدة لإمكانية الاستفادة من الماء الأرضي الصاعد بالخاصة الشعرية.